The Role of Price on Consumers of PT Jiva Samudra Biru: Product Quality and Design on Repurchase Intention - Sumardi, Cindy Aprilia; Asmin, Erny Amriani; Gunawan, Rachmat (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the effect of product quality and product design on repurchase intention through price as an intervening variable (case study on consumers of PT Jiva Samudra Biru). The sample in this study amounted to 384 people who were taken using a non-probability sampling technique with a purposive sampling method with the criteria of consumers who have purchased PT. Jiva Samudra Biru products (Bold and Ko) aged ≥ 20 years. The form of this research is descriptive and verification with the path analysis method. The results of the study show that: (1) product quality has a positive and significant effect on repurchase intention, (2) product design has a positive and significant effect on repurchase intention, (3) price has a positive and significant effect on repurchase intention, (4) product quality has a positive and significant effect on price, (5) product design has a positive and significant effect on price, (6) product quality has a positive and significant effect on repurchase intention through price, (7) product design has a positive and significant effect on repurchase intention through price.